2019
DOI: 10.1002/bdr2.1635
|View full text |Cite
|
Sign up to set email alerts
|

Absence of developmental and reproductive toxicity in animals exposed to dolutegravir

Abstract: The success of new antiretroviral medicines for HIV resulted in a change to guidelines of standard therapy where continuation of antiretroviral therapy is recommended to maintain the low viral load during pregnancy, thereby preventing transmission of the virus to the fetus. As a result, pregnancy related exposure to HIV medicines has increased. Understanding the safety of these medicines during pregnancy is of paramount importance to ensure health of mothers and their offspring; well-designed animal studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 9 publications
0
23
1
Order By: Relevance
“…Drugs that are known human teratogens often show teratogenic defects in animal models, although not always [16,17]. Pre-clinical reproductive toxicology studies conducted on rats and rabbits found no DTG-related effects on fertility, embryonic, or fetal development [18], although these studies did not mimic the clinical scenario as they included higher than clinically relevant DTG doses (40À1000 mg/kg/day), tested DTG alone and not as part of an ART regimen, and exposed animals to DTG in specific windows that did not include the entire pregnancy [18]. Given the uncertainty surrounding the link between DTG and NTDs in humans, and the limitations of the pre-clinical DTG fetotoxicity studies, further animal studies modeling the clinical scenario are merited.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs that are known human teratogens often show teratogenic defects in animal models, although not always [16,17]. Pre-clinical reproductive toxicology studies conducted on rats and rabbits found no DTG-related effects on fertility, embryonic, or fetal development [18], although these studies did not mimic the clinical scenario as they included higher than clinically relevant DTG doses (40À1000 mg/kg/day), tested DTG alone and not as part of an ART regimen, and exposed animals to DTG in specific windows that did not include the entire pregnancy [18]. Given the uncertainty surrounding the link between DTG and NTDs in humans, and the limitations of the pre-clinical DTG fetotoxicity studies, further animal studies modeling the clinical scenario are merited.…”
Section: Introductionmentioning
confidence: 99%
“…We think that it would be unscientific to dismiss our findings of a relationship between therapeutic levels of DTG-based ART and an increase in fetal defects simply because it does not fit the expectation of a classic dose response. We would also like to note that the one NTD observed in the rabbit fetotoxicity study by Stanislaus et al [3] was observed in the lowest DTG dose treatment arm.…”
mentioning
confidence: 76%
“…We chose a dose that yielded DTG Cmax concentrations similar to those seen in pregnant women (3000 ng/ml). Further, as the higher rates of NTDs were observed in women who received DTGbased ART from conception, we selected to treat our animals for the entire duration of pregnancy (unlike what was performed in the studies by Stanislaus et al [3]). Our control group was handled identically to the treated group (i.e.…”
mentioning
confidence: 99%
“…In the WEC in vitro model, embryos in the VYS are exposed directly to DTG in media, in contrast to an in vivo embryo‐fetal development (EFD) study whereby embryos are exposed to DTG via maternal blood passing through the placenta. In the rat EFD with DTG (Stanislaus et al, 2019), the mean Cmax value at the no observed adverse effect level (NOAEL) of 1,000 mg/kg/day was 108.9 μg/ml on GD 17. Although the scope of the current WEC study is limited, these results supplement the results from the EFD rat study by demonstrating that direct exposure of a mammalian embryo to DTG also did not result in developmental toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical animal studies conducted prior to original regulatory approval, DTG did not show developmental toxicity up to 30‐fold (rats) and 0.4‐fold (rabbits) the maximum human recommended dose (Stanislaus et al, 2019). These in vivo studies in rats and rabbits further confirm the latest emerging human data that is indicating an absence of a signal for NTDs in humans.…”
Section: Introductionmentioning
confidence: 99%